KINERJA SEKTOR PUBLIK DAN PENGUKURANNYA - Sugeng Hartanto (Jurnal Ilmiah Akuntansi Indonesia, 2018)
This study seeks to uncover various aspects contained in organizational performance, how the organization can be better and what factors influence it. In the study of theories from previous studies as revealed by Mahsun (2006) and Wibowo (2008) performance is a goal achievement. Then Pasolong (2010) argues that performance can be seen from two sides, namely individuals (employees) as well as from the organization. Some researchers state that organizational performance depends on individual performance, if the performance of each employee is good it will have a good impact on organizational performance. But the statement still cannot answer the aspects contained in the organization that can directly influence the achievement of organizational results. This study seeks to reveal what aspects can trigger organizational achievement in accordance with its objectives and how researchers see that it is an indicator that triggers good organizational performance that can be seen in terms of measurement. Keywords : Employee Performance, Organizational Performance, Performance Measurement, Public Sector